Magnetic properties of inner magnetosphere during geomagnetic storms inferred from a tsy ganenko magnetic field model - D.Y. Lee; K. C. Kim; C. R. Choi; H. J. Kim (Journal of Astronomy and Space Sciences, 2004)
In this paper we report some properties of inner magnetospheric structure inferred from the T01s code, one of the latest magnetospheric models by Tsyganenko. We have constructed three average storms representing moderate, strong, and severe intensity storms using 95 actual storms. The three storms are then modelled by the T01s code to examine differences in magnetic structure among them. We find that the magnetic structure of intense storms is strikingly different from the normal structure. First, when the storm intensity is large, the field lines anchored at dayside longitudinal sectors become warped tailward to align to the solar wind direction. This is particularly so for the field lines anchored at the longitudinal sectors from postnoon through dusk. Also while for the moderate storm the equatorial magnetic field near geosynchronous altitude is found to be weakest near midnight sector, this depression region expands into even late afternoon sector during the severe storm. Accordingly the field line curvature radius at the equator in the premidnight geosynchronous region becomes unusually small, reaching down to a value less than 500 km. We attribute this strong depression and the dawn-dusk asymmetry to the combined effect from the enhanced tail current and the westward expansion/rotation of the partial ring current.